Individuals with developmental disabilities make their own stylistic contributions to text written with physical facilitation - Nicoli, Giovanni; Pavon, Giulia; Grayson, Andy; Emerson, Anne; Cortelazzo, Michele; Mitra, Suvobrata (Frontiers in Child and Adolescent Psychiatry, 2023)
For individuals with developmental disabilities (DD) such as autism, Down syndrome, or cerebral palsy, learning to express with language is a two-fold challenge because atypical cognitive capacity is compounded by sensorimotor coordination deficits. One approach to assisting linguistic expression in these individuals is to physically support them, for example, by touching their torso or arm as they type. The neurophysiological mechanism of such motor assistance for linguistic expression is not known, but recently it has been proposed that light touch may reduce the cognitive load associated with the sensorimotor coordination of typing, thereby releasing shared cognitive resources to the task of generating content. Historically, there has been significant controversy over the extent to which the facilitator and not the user authors texts written with touch assistance. User groups and a few researchers have argued that the user can express their thoughts through such techniques, but the prevailing view among researchers is that these texts are entirely the by-products of the facilitators’ ideomotor cueing of users’ movements. If the user is not a source of the produced text, the only linguistic style detectable in the text should be the facilitator’s. Here, we use quantitative linguistic analysis to investigate whether DD users typing text with touch assistance exhibit their own stylistic signatures alongside those of their facilitators. In Study 1, we investigate whether the stylometric fingerprints of a set of users are detectable when they are all assisted by the same facilitator. In Study 2, we examine whether the users’ stylometric characteristics are retained even when they are assisted by multiple facilitators. Across both studies, the results show that the users’ stylistic signature is detectable alongside that of facilitators. This suggests that the texts generated by DD users with physical assistance should be viewed as co-authored rather than wholly authored by facilitators via ideomotor processes. The users’ stylometric presence in these texts suggests that touch-assistance may serve as a developmental scaffold and should be re-appraised as a teaching aid even where unassisted linguistic expression is an unlikely end goal.